miRNA profiling in leaf and cork tissues of Quercus suber reveals novel miRNAs and tissue-specific expression patterns - Chaves, Inês; Lin, Yao-Cheng; Pinto-Ricardo, C; de Peer, Yves; Miguel, Célia (TREE GENETICS & GENOMES, 2014)
The differentiation of cork (phellem) cells from the phellogen (cork cambium) is a secondary growth process observed in the cork oak tree conferring a unique ability to produce a thick layer of cork. At present, the molecular regulators of phellem differentiation are unknown. The previously documented involvement of microRNAs (miRNAs) in the regulation of developmental processes, including secondary growth, motivated the search for these regulators in cork oak tissues. We performed deep sequencing of the small RNA fraction obtained from cork oak leaves and differentiating phellem. RNA sequences with lengths of 19-25 nt derived from the two libraries were analysed, leading to the identification of 41 families of conserved miRNAs, of which the most abundant were miR167, miR165/166, miR396 and miR159. Thirty novel miRNA candidates were also unveiled, 11 of which were unique to leaves and 13 to phellem. Northern blot detection of a set of conserved and novel miRNAs confirmed their differential expression profile. Prediction and analysis of putative miRNA target genes provided clues regarding processes taking place in leaf and phellem tissues, but further experimental work will be needed for functional characterization. In conclusion, we here provide a first characterization of the miRNA population in a Fagacea species, and the comparative analysis of miRNA expression in leaf and phellem libraries represents an important step to uncovering specific regulatory networks controlling phellem differentiation.
Keywords: miRNA; phellem; Quercus suber; secondary growth; Small RNA; Tree

Reference Gene Selection for Quantitative Real-time PCR Normalization in Quercus suber - Marum, Liliana; Miguel, Andreia; Ricardo, Cândido P.; Miguel, Célia (PLoS ONE, 2012)
The use of reverse transcription quantitative PCR technology to assess gene expression levels requires an accurate normalization of data in order to avoid misinterpretation of experimental results and erroneous analyses. Despite being the focus of several transcriptomics projects, oaks, and particularly cork oak (Quercus suber), have not been investigated regarding the identification of reference genes suitable for the normalization of real-time quantitative PCR data. In this study, ten candidate reference genes (Act, CACs, EF-1α, GAPDH, His3, PsaH, Sand, PP2A, ß-Tub and Ubq) were evaluated to determine the most stable internal reference for quantitative PCR normalization in cork oak. The transcript abundance of these genes was analysed in several tissues of cork oak, including leaves, reproduction cork, and periderm from branches at different developmental stages (1-, 2-, and 3-year old) or collected in different dates (active growth period versus dormancy). The three statistical methods (geNorm, NormFinder, and CV method) used in the evaluation of the most suitable combination of reference genes identified Act and CACs as the most stable candidates when all the samples were analysed together, while ß-Tub and PsaH showed the lowest expression stability. However, when different tissues, developmental stages, and collection dates were analysed separately, the reference genes exhibited some variation in their expression levels. In this study, and for the first time, we have identified and validated reference genes in cork oak that can be used for quantification of target gene expression in different tissues and experimental conditions and will be useful as a starting point for gene expression studies in other oaks.
The following values have no corresponding Zotero field: publisher: Public Library of Science
Keywords: Cork oak; Gene expression; reference genes; RT-qPCR (voyant)

Genetic divergence in Cork Oak based on cpDNA sequence data - Costa, Joana; Miguel, Célia; Almeida, Helena; Oliveira, Margarida M.; Matos, José a; Simões, Fernanda; Veloso, Manuela; Ricardo, Pinto C.; Paulo, Octávio S.; Batista, Dora (BMC Proceedings, 2011)
The following values have no corresponding Zotero field: periodical: BMC Proceedings issue: Suppl 7
Keywords: Cork oak; cpDNA (voyant); genetic diversity; Populations